Incidence of oxygen desaturation with intravenous ketamine and the effects of the basic airway management maneuvers on it - Lamgade, Amit; Joshi, A; Kharel, S; McArthur, L (Journal of General Practice and Emergency Medicine of Nepal, 2010)
Introduction: This study was conducted to evaluate and compare the incidence of oxygen desaturation during intravenous ketamine for short surgical procedure and the effects of basic airway management maneuvers during desaturation. Methods: A Population based comparative study was done at two different hospitals situated in hilly regions of Nepal. Children aged between 3 months and 14 years were observed for their oxygen saturation with the help of Pulse Oxymeter during intravenous ketamine anesthesia for short surgical procedures lasting less than 15 minutes. Results: Seventy nine patients from United Mission Hospital (UMN), Tansen and 66 patients from Okhaldhunga Community Hospital (OCH), Okhadhunga were enrolled; the incidence of desaturation was 8(10%) and 11(16.1%) in Tansen and Okhaldhunga respectively. 7(87.5%) and 8(72.7%) of the patients with desaturation from UMH and OCH respectively, were improved to >90% with chin lift only and rest needed jaw thrust. Conclusion: The incidence of oxygen desaturation is common within first few minutes of ketamine administration. Basic airway measures like chin lift and jaw thrust is enough to improve oxygen saturation.